Communique - Fekete, Albert (4D Journal of Landscape Architecture and Garden Art, 2018)
The Faculty of Landscape Architecture and Urbanism declares 2019 as a centennial memorial year in order for us to notably commemorate two of the faculty’s prominent figures’ 100th birth anniversaries, that of Professor Mihály Mőcsényi and our art teacher András Balogh.